2001
DOI: 10.1016/s1074-7613(01)00191-1
|View full text |Cite
|
Sign up to set email alerts
|

OX40 Promotes Bcl-xL and Bcl-2 Expression and Is Essential for Long-Term Survival of CD4 T Cells

Abstract: It is important to understand which molecules are essential for long-lived immunity. We show that OX40 (CD134) is required with CD28 for the survival of CD4 T cells following antigen-driven expansion. In contrast to CD28-/- T cells, which show defects early, OX40-/- T cells are relatively unimpaired in IL-2 production, cell division, and expansion. However, OX40-/- T cells fail to maintain high levels of Bcl-xL and Bcl-2 4-8 days after activation, and undergo apoptosis. Conversely, OX40 stimulation promotes Bc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
553
5
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 598 publications
(589 citation statements)
references
References 67 publications
25
553
5
1
Order By: Relevance
“…Contrary to Treg cells, effector T cells express OX40 only upon activation [11,59]. We found that Tem cells, representing the most abundant TIL subset, highly expressed OX40.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Contrary to Treg cells, effector T cells express OX40 only upon activation [11,59]. We found that Tem cells, representing the most abundant TIL subset, highly expressed OX40.…”
Section: Discussionmentioning
confidence: 70%
“…OX40 is a costimulatory molecule constitutively expressed by Treg cells and expressed upon activation by T effector (Teff) cells. Triggering of OX40 has opposite effects on these two T-cell populations: Treg cells are inhibited in their suppressive functions [3][4][5][6], while Teff cells are stimulated to proliferate, survive and gain memory phenotype [7][8][9][10][11]. Treatment of different types of mouse transplantable tumors with the mAb OX86, the agonist of OX40, favors tumor rejection thanks to its double effect on Treg and Teff cells [3,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, whether or not this regulation was dependent on mammalian target of rapamycin pathway is still controversial (13,75). CD28 also promotes expression of bcl-2, bfl-1 (A1), and myeloid cell leukemia sequence 1 (mcl-1) to regulate T cell survival (76)(77)(78).…”
Section: Cell Survivalmentioning
confidence: 99%
“…OX40 regulates T cell survival by sustaining PKB mediated expression of bcl-2 and bcl-xL (15,76). Upon interaction with its ligand--OX40L, the cytoplasmic tail of OX40 associates with an adapter protein TRAF2 (79) to mediate signal transduction, probably through PI3K/PKB/ NF-κB pathway then regulates expression of bcl-xL, A1, and bcl-2 that controls T cell longevity (4).…”
Section: Cell Survivalmentioning
confidence: 99%
See 1 more Smart Citation